INTRODUCTION AND MARKETING OF LOCAL NATURAL TOURISM POTENTIAL PEMATANG VILLAGE, NORTH LABUHANBATU REGENCYTHROUGH SOCIAL MEDIA - Aperius Zega; Pristiyono; Abdillah Menri Munthe (RADJA PUBLIKA, 2025)
Social media has penetrated into many parts of people's lives, including influencing the way tourists conduct tourism activities in Pematang Village. This study aims to understand the contribution of social media in promoting tourism in Pematang Village and to formulate steps to optimize social media as a tourism promotion tool. The method used in this study is descriptive qualitative with data collection methods of observation, documentation and interviews with tourists and the community around the tourist attractions of Pematang Village. The data analysis technique used is SWOT analysis in SWOT analysis there are external factors consisting of opportunities and threats and internal factors consisting of strengths and weaknesses.